2019
DOI: 10.4049/jimmunol.1900132
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide Downregulates 11β-Hydroxysteroid Dehydrogenase 2 Expression through Inhibiting Peroxisome Proliferator–Activated Receptor-γ in Placental Trophoblasts

Abstract: It is increasingly recognized that excessive glucocorticoids induce fetal intrauterine growth restriction (IUGR). Placental 11bhydroxysteroid dehydrogenase 2 (11b-HSD2), a glucocorticoid-catalyzing enzyme, prevents active glucocorticoids from maternal circulation into the fetus, thus protecting against IUGR. Previous studies demonstrated gestational LPS exposure caused fetal IUGR. The aim of the current study was to investigate the effects of LPS on 11b-HSD2 in mice placentas and human placental trophoblasts. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 61 publications
(72 reference statements)
0
19
0
Order By: Relevance
“…The article found that nuclear translocation of PPAR‐γ and NF‐κB p65 was remarkably elevated in mononuclear sinusoidal trophoblast giant cells of the labyrinth layer. Our recent study found that lipopolysaccharide exposure inhibited placental PPAR‐γ and its downstream gene 11β‐HSD2 via promoting the interaction between NF‐κB p65 and PPAR‐γ in the cytoplasm and nucleus of the placental trophoblast 14 . These results provide mechanistic explanation by which inflammation inhibits placental 11β‐HSD2 in SGA infants.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…The article found that nuclear translocation of PPAR‐γ and NF‐κB p65 was remarkably elevated in mononuclear sinusoidal trophoblast giant cells of the labyrinth layer. Our recent study found that lipopolysaccharide exposure inhibited placental PPAR‐γ and its downstream gene 11β‐HSD2 via promoting the interaction between NF‐κB p65 and PPAR‐γ in the cytoplasm and nucleus of the placental trophoblast 14 . These results provide mechanistic explanation by which inflammation inhibits placental 11β‐HSD2 in SGA infants.…”
Section: Discussionmentioning
confidence: 76%
“…Peroxisome proliferator‐activated receptor gamma, a ligand‐activated nuclear receptor, involves in placental development. The in vitro studies demonstrated that activated PPAR‐γ upregulated 11β‐HSD2 in human placental trophoblasts 13,14 . A population‐based case‐control study found that PPAR‐γ protein and mRNA levels were decreased in SGA placentas 12 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Placental 11β-hydroxysteroid dehydrogenase 2 (HSD2), a glucocorticoid-catalysing enzyme, protects against foetal growth restriction by preventing active glucocorticoids present in the maternal circulation from entering the foetal circulation. In a recent study, bacterial LPS was shown to downregulate 11β-HSD2 by suppressing proliferator-activated receptor-γ in placental trophoblasts 27 . This may contribute to excessive glucocorticoid production, resulting in LPS-induced foetal growth restriction.…”
Section: Discussionmentioning
confidence: 97%
“…Human S100A8 and scrambled siRNAs were obtained from Gene Pharma Corp (Shanghai, China). The S100A8 siRNA sequences was as follows: (sense, 5′-GGUCACUACUGAGUGCCCUCAGUUU--3′; antisense, 5′-AAACUGAGGGCACUCAGUAGUGACC-3′); The RNA interference protocol was on the basis of the previous study [24]. Human S100A8-siRNA was transfected into cells using Lipofectamine 3000 according to the manufacturer's instructions (Invitrogen, Carlsbad, CA, United States).…”
Section: Small Interfering Rna (Sirna) Transfectionmentioning
confidence: 99%